Mouse maternal odontogenic infection with Porphyromonas gingivalis induces cognitive decline in offspring - Eri Ishida; Hisako Furusho; Ting-Yi Renn; Fumie Shiba; Hung-Ming Chang; Hiroshi Oue; Ryuji Terayama; Yukio Ago; Kazuhiro Tsuga; Mutsumi Miyauchi (Frontiers Media S.A., 2023)
IntroductionPorphyromonas gingivalis (P. gingivalis), a major periodontal pathogen, causes intrauterine infection/inflammation. Offspring exposed to intrauterine infection/inflammation have an increased risk of neurological disorders, regardless of gestational age. However, the relationship between maternal periodontitis and offspring functional/histological changes in the brain has not yet been elucidated.MethodsIn this study, we used a gestational mouse model to investigate the effects of maternal odontogenic infection of P. gingivalis on offspring behavior and brain tissue.ResultsThe step-through passive avoidance test showed that the latency of the acquisition trial was significantly shorter in the P. gingivalis group (p < 0.05), but no difference in spontaneous motor/exploratory parameters by open-field test. P. gingivalis was diffusely distributed throughout the brain, especially in the hippocampus. In the hippocampus and amygdala, the numbers of neuron cells and cyclic adenosine monophosphate response element binding protein-positive cells were significantly reduced (p < 0.05), whereas the number of ionized calcium binding adapter protein 1-positive microglia was significantly increased (p < 0.05). In the hippocampus, the number of glial fibrillary acidic protein-positive astrocytes was also significantly increased (p < 0.05).DiscussionThe offspring of P. gingivalis-infected mothers have reduced cognitive function. Neurodegeneration/neuroinflammation in the hippocampus and amygdala may be caused by P. gingivalis infection, which is maternally transmitted. The importance of eliminating maternal P. gingivalis-odontogenic infection before or during gestation in maintenance healthy brain function in offspring should be addressed in near future.